Are State-Owned Enterprises (SOEs) catalysts for or inhibitors of South African economic growth? - Madumi, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
There is no doubt that State-owned enterprises (SOEs) play an important role in fostering economic growth, globally. Moreover, in South Africa, basic services such as water, electricity, sanitation, and transportation are provided by the state through the SOEs. Against this backdrop, most of these SOEs in South Africa have fallen into complete disarray and they are characterized by the upsurge in unbridled corruption. Whilst corruption is perceived to be on the rise, state capture is one of today’s most widely discussed and controversial issues that is affecting these corporations and it is allowing corruption to thrive. Put simply, SOEs in South Africa are misgoverned. South Africa is in a period of low growth, which is likely to continue for the next few years. South Africa’s GDP growth is currently below 2%, which not ideal to produce sustainable growth. Undeniably, South Africa is plagued by economic challenges such as lack of service delivery, poor financial management, weak business confidence, low growth, massive unemployment, and corruption which are threats to the economic and financial sustainability of the country. Arguably, if the government is serious in solving these economic challenges, drastic action is required to stimulate economic growth, investment and ultimately creating jobs. The role of SOEs is well-embedded in scholarly arguments, however, there is very little attention paid to the impact of reckless and mismanagement of SOEs in South Africa. Using economic theories relating to SOEs as a conceptual framework, this chapter analyses the economic growth and determines the impact of the SOEs’ mismanagement of economic growth and investment in South Africa. It concludes that SOEs can make an essential contribution to the economy, but most of South Africa’s SOEs need a serious reform because they are currently negating the economic growth of the country.
Journal article published in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Economic growth; Market Failure; Corruption; State-owned enterprises; Sustainability; Government business enterprises; Corruption; Sustainable development; Economic development